Practical biology laboratory manual and report - Mohd Nasohah, Nor Sa'adah; Hamzah, Haliza; Teruk, Kamaril Azlah; Mohd Sani, Rositi Mashani; Zahari, Shafiyyah Solehah; Jamaludin, Rosmarina (IIUM Press, 2021)
This laboratory manual is organized into ten chapters. Each chapter is provided with a worksheet, which is to be used by the students to report the experimental results. The experiments are designed to enhance students’ knowledge and understanding of biology and biological issues thus the experiments are related to topics in Biology 1 and Biology 2 courses.